Analisis Perlindungan Hukum Terhadap Hak Restitusi Korban Kekerasan Seksual (International Forum of Researchers and Lecturers, 2025)
Sexual Violence against children is a serious problem that requires in-depth attention in the context of legal protection of victim. In the case of Herry Wirawan, involving 13 (thirteen) victims of sexual assault in Bandung, has raised controversy over the reimbursement charged to the state. In it’s ruling, the chamber of Judges of PN Bandung sentenced Herry Wirawan to life sentence and ordered the payment of restitution to the victims. However, there are questions about the legality of the payment of restitution, especially since the perpetrators have been sentenced to life imprisonment, which is incompatible with Article 67 2023 of the Covenant. This study uses a normative approach to analyze this problem, focusing one the case of Herry Wirawan. The result showed a gap between the legal process and the victim’s need to obtain adequate compensation for the suffering they suffered. In addition, there are problems related to the minimality of the claim for restitution made by the victim and the implementation of restitution that is not always smooth. Implementation of restitution in legal practice still faces a minimum victim awareness and understanding of their rights as well as the perpetrator’s ability to pay restitution. The study highlights the need to raise victim awareness, improve law enforcement mechanism, and provide adequate support service. In addition, recommendations for improvement of relevant policy or legal practice are also identified. It is hoped that this research can contribute to understanding the complexity of the restitution process in cases of sexual violence in Indonesia and provide a basis for improving legal protection for victims.